Numerical Simulation of Hydrodynamic Characteristics of YuanyangIsland in Liao River Estuary Based on FVCOM - LI Jin; XU Tianping; ZHANG Mingliang (Renmin Zhujiang)
Based on an unstructured grid, finite-volume coastal ocean model (FVCOM), a high-resolution numerical model is established to study the hydrodynamic characteristics of Yuanyang Island in Liao River Estuary. The calculation accuracy and reliability of the model are verified by the measured data such as tidal level, flow velocity, and flow direction. After comparison, the results show that the calculated values by the model are in good agreement with the measured values. On the basis of verifying the reliability of the model, this paper simulates the flow fields of Yuanyang Island under different runoff conditions and briefly analyzes the variations of the hydrodynamic and flow fields under different runoff conditions. The simulated flow fields reveal the complex flow conditions of Yuanyang Island in Liao River Estuary, which provides a reference for further study of salinity distribution, sediment scouring and silting, and pollutant transport in estuarine wetland.